(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
Sima Qian, the creator of the Chinese science of history (II-I centuries), stated that "perception is possible through classification" ("Shi Tzi"). The essence of this phenomenon is that the same schemes of classification (lian i, san tsai, u xin, etc.) spread to all areas of culture: mythology and religion, philosophy, chronography and history, cosmology, cosmogony, cosmography and geography, astronomy and astrology, mathematics, chemistry and alchemy, medicine, literature, music, theater, architecture, visual and martial arts, politics, money, clothing, cooking, economics, and more.